“Отчизна”, “ойчизна” в українських писемних джерелах ранньомодерної доби - Ніка, Оксана Іванівна (Київський національний університет імені Тараса Шевченка, 2022)
Схарактеризовано досвід вивчення слова/концепту/поняття/ терміна «отчизна», «ойчизна» в історичних і філософських працях, присвячених ранньомодерному українському періоду, у дослідженнях із когнітивної лінгвістики, лінгвокультурології. Проаналізовано слова «отчизна», «ойчизна» на позначення ʻрідна земляʼ та ʻpatriaʼ, а також словосполуку «отчизна небесная» ʻЦарство Небеснеʼ в українських словниках і текстах (панегіричні, геральдичні вірші, проповіді) ХVІІ ст. Встановлено текстове домінування смислів, що визначають колективно-соціальний, інтерперсональний простір суб’єкта/суб’єктів (отчизна/очизна, ойчизна ʻpatriaʼ). Концептуальні ознаки вербалізовані як «вольность отчизни», «цілость отчизни», «любов отчизни». Розуміння і сприйняття «отчизни» як території, яку потрібно захищати, репрезентовано в смислових відношеннях «неухильно виконувати свій громадянський обов’язок перед отчизною», «необхідно захищати отчизну» та ін.

The article analyses the words оtchyzna (fatherland), оіchyzna (homeland) to denote ʻnative landʼ and ʻpatriaʼ, the phrase оtchyzna nebesnaia (fatherland heavenly) «Kingdom of Heaven» in dictionaries and texts of the 17th century. The experience of studying the word / concept / notion / term оtchyzna (fatherland) is characterized according to the historical and philosophical works, research in cognitive linguistics, linguocultural studies. The conclusion about the latent ethnomynicity and semantic hybridity of the concept of оtchyzna (fatherland) is confirmed. The meaning of the word оtchyzna (fatherland) ʻnative landʼ, which denotes the personal, individual space of the subject, оtchyzna (fatherland), оichyzna (homeland) ʻpatriaʼ as a collective-social, interpersonal space for the people who inhabit it. The first of them is associated with the use of Ukrainian nouns zemlia (land), rod (family), dom ottsa (father's house), pronoun adjective moia (my), adjective vlasnyi (own). Conceptual features specify the place of birth of the subject, parental home, family. side, to society / people. The word оtchyzna (fatherland) ʻpatriaʼ is combined with the attributes of nasha (our), mylaia (dear), functions in a constant expression za сhest bozhuiu (for the honour of God), za viru sviatuiu (for the holy faith), zа оtchyznu myluiu (for the dear homeland), combined with predicates of urodyla (she gave birth to someone), vykhovala (she brought up someone), oboimuiet (she embraces someone), creating a metaphorical series that correlates with the image of the mother. In this sense, dom otchyznyi (fatherland’s house), оtchyzny dom (fatherland’s house), оichyzna (homeland) (the latter – in the first half of the 17th century) are also used. The perception of оtchyzna (fatherland) as a territory to be protected is represented in the semantic relations of "steadily fulfilling one's civic duty to the fatherland" sluzhyty otchyzni (to serve the fatherland); "to be faithful, devoted to the fatherland" virne sluzhyty (to serve faithfully); "it is necessary to defend the homeland" оtchyznu boronyty (to defend the homeland), prolyvaty krov (to shed blood), "civic duty dominates personal values". Conceptual features are verbalized as «volnost оtchyzny» («freedom of the fatherland»), «tsilisnist оtchyzny» («the integrity of the fatherland»), «pozhytechnist nauky dlia оtchyzny» («the usefulness of science for the fatherland»), «liubov оtchyzny» («the love of the fatherland»), defined as the collective and social values of Ukrainians of the 17th century.
«Оtchyzna» («fatherland»), «оichyzna» («homeland») in ukrainian written sources of early modern era
Keywords: «отчизна»; «ойчизна»; колективно-соціальний & персональний простір; вербалізація; українські писемні джерела ранньомодерної доби; оtchyzna (fatherland); оichyzna (homeland); collective-social & personal space; verbalization; Ukrainian written sources of the early modern period